Elsewhere, U.S.A - Conley, Dalton 1969- (New York Pantheon Books, 2009)
Examining the dramatic changes that have occurred in American society over the past three decades, the author of The Pecking Order offers a thoughtful study of the new social realities of life, explaining how the social, economic, and technological transformation has reshaped individual lives
Preface: A tale of three generations -- Introduction: Life among the elsewhere class -- From the Protestant ethic to the elsewhere ethic -- And you may find yourself behind the wheel of a large automobile : from General Motors to Google -- One plus a hundred zeros : welcome to your (n)office -- Convestment : the way we earn and spend -- Shoot the moon : public life in an age of private markets -- From elsewhere to nowhere : crime and punishment -- Polymorphous perversity : family life in the elsewhere society -- The birth of the intravidual -- Conclusion: Learning to love the BlackBerry
Includes bibliographical references (p. 195-207) and index
1
Keywords: Economic indicators; Social change; Social indicators; Social problems; Social structure